Vì: f(1) = 5 nên ta có: a.1 + b = 5 hay a + b = 5 ( 1 )
f(-1) = 1 nên ta có: a.(-1) + b = 1 hay -a + b = 1 ( 2 )
Từ ( 1 ) và ( 2 ) => 2b = 6 => b = 3 => a = 2
Vậy f(x) = 2x+3
Đúng 0
Bình luận (0)
\(f\left(x\right)=ax+b\)
\(\Rightarrow f\left(1\right)=a+b\)
Mà \(f\left(1\right)=5\)
\(\Rightarrow a+b=5\left(1\right)\)
Lại có \(f\left(-1\right)=-a+b\)
Mà \(f\left(-1\right)=1\)
\(\Rightarrow-a+b=1\left(2\right)\)
Lấy (1) cộng (2) ta được :
\(2b=6\)
\(b=3\)
Thay b=3 vào (1) ta được a= 2
Vậy a=2 và b=3
Đúng 0
Bình luận (0)